2017
DOI: 10.1039/c7fo00159b
|View full text |Cite
|
Sign up to set email alerts
|

Oil-in-water emulsions stabilised by cellulose ethers: stability, structure and in vitro digestion

Abstract: The effect of cellulose ethers in oil-in-water emulsions on stability during storage and on texture, microstructure and lipid digestibility during in vitro gastrointestinal digestion was investigated. All the cellulose ether emulsions showed good physical and oxidative stability during storage. In particular, the methylcellulose with high methoxyl substituents (HMC) made it possible to obtain emulsions with high consistency which remained almost unchanged during gastric digestion, and thus could enhance fullne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…For all the samples, G 0 value was always greater than G 00 within the scope of the linear viscoelastic region (LVR) indicating the "solid" dominant behavior of the emulsions and the emulsions are highly structured. [30] For MC emulsions, G 0 and G 00 showed overshoots before sudden drops, which was due to the destruction of the related structure.…”
Section: Rheological Characterization Of Emulsionsmentioning
confidence: 96%
See 1 more Smart Citation
“…For all the samples, G 0 value was always greater than G 00 within the scope of the linear viscoelastic region (LVR) indicating the "solid" dominant behavior of the emulsions and the emulsions are highly structured. [30] For MC emulsions, G 0 and G 00 showed overshoots before sudden drops, which was due to the destruction of the related structure.…”
Section: Rheological Characterization Of Emulsionsmentioning
confidence: 96%
“…HPMC, MC, and XG are all food-approved edible materials. Borreani et al [30] reported that oxidation stability of HPMC emulsion was better than MC due to their better adsorption ability on the interface which acted as a physical barrier to protect the oil. The proposed emulsification mechanism was that HPMC aqueous solution was first mixed with soybean oil, and HPMC molecules could be adsorbed at the surface of oil droplet.…”
Section: Microstructure Of Emulsionsmentioning
confidence: 99%
“…A gradual increase in k 232 and k 270 values throughout storage was detected for all the samples (Table 3) as previously observed by other authors. Bouaziz et al (2008) and Borreani et al (2017) observed a regular increase in k 232 and k 270 values as a function of storage for olive oils and for emulsions elaborated with HPMC and sunflower oil, respectively. Moreover, the values were significantly lower for vacuum dried oleogels than for conventionally dried, when comparing same type of oil.…”
Section: Oxidative Stability Of Oleogelsmentioning
confidence: 91%
“…The digestion process in the human gastrointestinal tract is simulated through an in vitro digestion model, which was a modified version of that described by Borreani et al () and Qiu, Zhao et al ().…”
Section: Methodsmentioning
confidence: 99%